ANALISIS TINGKAT EFISIENSI BIAYA PADA PELAKU USAHA BATU BATA MERAH DILIHAT DARI SEGI PENDAPATAN DI DESA KEMBIRITAN KECAMATAN GENTENG KABUPATEN BANYUWANGI - Bayu Sasmita Aji; Bambang Suyadi; Titin Kartini (Economic Education, University of Jember, 2017)
This study aims to examine more deeply about the analysis of the level of cost efficiency in red brick business actors in terms of revenue in the Village District Kembiritan Genteng Banyuwangi. The type of research used in this study is quantitative. Place of study is determined by purposive area, that is in Kembiritan Village of Genteng District of Banyuwangi Regency. The subjects used in this study are red brick business actors in Kembiritan Village, Genteng District, Banyuwangi Regency with the criteria of red brick business run for less than 3 years. The data in this study were obtained by document, interview and observation. The analysis used in this research is anilisis efficiency by using formula R / C that is income received divided by cost incurred. After the results obtained value of efficiency ratio, it can be known the value of the level of efficiency is low and medium. The final result of this research can be concluded that four red brick business actors in Kembiritan Village of Genteng District of Banyuwangi Regency are seen from the aspect of income can reach efficient level. The level of efficiency achieved by four red brick business actors in Kembiritan Village, Genteng District, Banyuwangi Regency is one with low efficient category with R / C ratio of 1.27 and three red brick business actors with high efficient category with value R / C ratio of 1.37, 1.38 and 1.38.